Insomnia Polygenic Component on Attention Deficit-Hyperactivity Disorder: Exploring this Association Using Genomic Data from Brazilian Families - Carpena, Marina Xavier; Fraga, Brenda Barbon; Martins-Silva, Thais; Salatino-Oliveira, Angélica; Genro, Júlia Pasqualini; Polanczyk, Guilherme V.; Zeni, Cristian; Schmitz, Marcelo; Chazan, Rodrigo; Hutz, Mara Helena; Rohde, Luis Augusto; Tovo-Rodrigues, Luciana (Sleep Science, 2024)
Introduction Insomnia is highly prevalent among individuals with Attention-Deficit/Hyperactivity Disorder (ADHD). However, the biological mechanisms shared between both conditions is still elusive. We aimed to investigate whether insomnia's genomic component is able to predict ADHD in childhood and adolescence.Methods A Brazilian sample of 259 ADHD probands and their biological parents were included in the study. Their genomic DNA genotypes were used to construct the polygenic risk score for insomnia (Insomnia PRS), using the largest GWAS summary statistics as a discovery sample. The association was tested using logistic regression, under a case-pseudocontrol design.Results Insomnia PRS was nominally associated with ADHD (OR = 1.228, p = 0.022), showing that the alleles that increase the risk for insomnia also increase the risk for ADHD.Discussion Our results suggest that genetic factors associated with insomnia may play a role in the ADHD genetic etiology, with both phenotypes likely to have a shared genetic mechanism.
Keywords: polygenic risk score; insomnia; attention-deficit/hyperactivity disorder